Assessing Natural Incidence of Resident Pupal Parasitoids on the Drosophila suzukii (Diptera: Drosophilidae) Population in Non-crop Fruits - Buonocore Biancheri, María Josefina (2024)
Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), world-renowned as spotted-wing drosophila, is an invasive pest mainly affecting healthy, soft and stone fruit crops throughout Argentinian fruit-growing regions. Natural environments overgrown by exotic feral host plants apparently favour D. suzukii proliferation. This is common in the subtropical northwestern Argentina’s berry-producing region. An assemblage of resident parasitoid species has been associated with D. suzukii in crop and non-crop areas of Tucumán, the Argentina’s leading berries producer and exporter. Consequently, the hypothesis that the combined action of two pupal parasitoid species, Pachycrepoideus vindemiae Rondani (Hymenoptera: Pteromalidae) and Trichopria anastrephae Lima (Hymenoptera: Diapriidae), occurring in non-crop fruit areas, has a significant impact on D. suzukii natural regulation in such invaded habitats was tested. A survey of D. suzukii puparia from both feral peach [Prunus persica (L.) Batsch] (Rosaceae) and guava (Psydium guajava L.) (Myrtaceae) fallen fruits and soil surrounding them was performed in a wilderness area of Tucumán. Abundance of D. suzukii and associated parasitoids, and parasitism levels were assessed. Whole of 3437 D. suzukii puparia were recovered; 78% and 22% were surveyed from fruits and soil underneath the fruit, respectively. Tested fruits are important D. suzukii multiplying hosts. Both P. vindemiae and T. anastrephae accounted for 99.8% of total parasitoid individuals. Pupal parasitoids contribute to the D. suzukii natural mortality, as they killed a quarter of all puparia. Mostly T. anastrephae foraged on host puparia located in the fruit and P. vindemiae in both microhabitats. This information supports an augmentative biological control strategy in non-crop areas.